Postharvest Technology of Information Systems in Deli Serdang - Andre Gromico Napitupulu; Saipul Bahri Daulay; Ainun Rohanah (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Postharvest Technology of information systems in Deli Serdang regency done manually, resulting in information storage and processing systems is ineffective and inefficient. In information management is still largely a result of human use role requires a relatively longer time. More than that, the information seekers-and decision-makers also have difficulty in obtaining the data they need. Therefore it is necessary for the further development of the information system. Web-based information system is considered to be a solution in order to access information faster, systematic and easy to use. For that designed a web-based information systems in the management of Postharvest Technology of information systems in Deli Serdang regency. Postharvest Technology information system is designed using PHP programming language, MySQL database and the method of system development lifecycle (SDLC). Keywords: agricultural machinery Deli Serdang, information systems, post-harvest technology, web